Hijacking of Embryonic Programs by Neural Crest-Derived Neuroblastoma: From Physiological Migration to Metastatic Dissemination - Delloye-Bourgeois, Céline; Castellani, Valérie (Frontiers in Molecular Neuroscience, 2019)
In the developing organism, complex molecular programs orchestrate the generation of cells in adequate numbers, drive them to migrate along the correct pathways towards appropriate territories, eliminate superfluous cells, and induce terminal differentiation of survivors into the appropriate cell-types. Despite strict controls constraining developmental processes, malignancies can emerge in still immature organisms. This is the case of Neuroblastoma (NB), a highly heterogeneous disease, predominantly affecting children before the age of 5 years. Highly metastatic forms represent half of the cases and are diagnosed when disseminated foci are detectable. Neuroblastoma arise from a transient population of embryonic cells, the neural crest (NC), and especially NC committed to the establishment of the sympatho-adrenal tissues. The NC is generated at the dorsal edge of the neural tube of the vertebrate embryo, under the action of NC specifier gene programs. NC cells (NCC) undergo an epithelial to mesenchymal transition, and engage on a remarkable journey in the developing embryo, contributing to a plethora of cell-types and tissues. Various NCC sub-populations and derived lineages adopt specific migratory behaviors, moving individually as well as collectively, exploiting the different embryonic substrates they encounter along their path. Here we discuss how the specific features of NCC in development are re-iterated during NB metastatic behaviors.